2019
DOI: 10.1139/cjas-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microencapsulated complex of organic acids and essential oils on growth performance, nutrient retention, blood profiles, fecal microflora, and lean meat percentage in weaning to finishing pigs

Abstract: A total of 90 pigs (6.47 ± 0.27 kg; 21 d of age) were used in this 22 wk feeding trial to evaluate the effect of microencapsulated complex of organic acids and essential oils (MOE) on growth performance, nutrient retention, blood profile, fecal microflora, and lean meat percentage in pigs. Pigs were randomly distributed to one of three treatment groups (six replicate pens per treatment, five pigs per pen). Dietary treatments were CON, basal diet; MOE1, basal + 0.1% MOE; and MOE2, basal diet + 0.2% MOE. The ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
3
13
1
1
Order By: Relevance
“…Therefore, HA might be able to improve the immune system (Wenk, 2003). Oh et al (2018) have reported that consumption of HA does not alter WBC in pigs. In the present study, we found that BLP and HA had beneficial effects on blood lipid profiles and immune function, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, HA might be able to improve the immune system (Wenk, 2003). Oh et al (2018) have reported that consumption of HA does not alter WBC in pigs. In the present study, we found that BLP and HA had beneficial effects on blood lipid profiles and immune function, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…For growing pigs higher ADG, ADFI and gain:feed ratio were recorded for all the doses, while increased BW was reported for the highest dose. All the pigs showed improved meat quality (143) . They also tested this blend in combination with microencapsulated zinc oxide, reporting a reduction in E. coli count (144) .…”
Section: Terpenesmentioning
confidence: 92%
“…Moreover, vanillin activates the TRPV3 channel, like thymol and carvacrol (41) , whose activation, at the intestinal level, seems to trigger the release of serotonin which controls gut motility and chloride secretion by enterocytes, as mentioned before (147) . As stated in the thymol paragraph, many studies have reported positive effects (performance, reduction in pathogens count, maturation of the intestinal mucosa, decrease of local and systemic inflammatory pressure) in poultry and pigs fed a blend of vanillin, thymol and organic acids microencapsulated in a lipid matrix (35,(142)(143)(144)(145) (Table 1).…”
Section: Aldehydesmentioning
confidence: 99%
“…Thyme essential oil has been proved to inactivate the Salmonella enteritidis on ready to eat turkey meat products during preservation [ 61 ]. Microencapsulated complex of organic acids and essential oils (thymol 1.7% and vanillin 1.0%) at 0.2% level could improve red color value of meat and decreased drip loss about 30% percent in weaning to finishing pigs [ 62 ]. In addition, oregano ( Origanum vulgare ) essential oil at 0.2% level could improve the oxidative stability of meat in pigs [ 63 ].…”
Section: Introductionmentioning
confidence: 99%